Lubomír Doležel and his Legacy to Digital Humanities - Změlík, Richard (Bohemistyka, 2023)
The study focuses on that part of Lubomír Doležel’s scientific legacy which is connected with the application of quantitative and statistical methods in linguistics and literary science. In the early 1960s, the influence of information theory and cybernetics began to be strongly felt in the context of these disciplines. Alongside Jiří Levý, Lubomír Doležel was one of several linguistic researchers who creatively rethought the possibilities of these disciplines, among others, in literary science. This interest lasted, to varying degrees of intensity, until the 1980s. Although this phase of Doležel’s scholarship is usually neglected at the expense of his other works, for which he eventually became known as a world-class literary theorist, their importance is confirmed today, when quantitative methods are beginning to be used again in literary scholarship in general in the context of the digitial humanities. This study focuses not only on Doležel’s legacy to today’s literary scholarship in the digital humanities, which works with these methods, but above all highlights those of his ideas that, seen through today’s lens, have become literally timeless in this context.